Evaluation of an Electric Vehicle Ride Dynamics under ISO- 2631 Criteria - ., Ubaidillah; Candra, Ipnu; Bagus Wiranto, Ilham (International Journal of Engineering and Technology, 2018)
The work is aimed to study the vertical response of ride performance of an electric vehicle. The issues related to the design of vehicle model with passive suspension system are discussed. A full-car seven-degree-of-freedom model is used to investigate the dynamics re- sponse by applying road disturbances in sinusoidal road input excitation. The time response of the heave, roll, and pitch of the sprung mass is obtained for the need of studying the effect of given variation of both suspension stiffness coefficient and suspension damping coefficient. Finally, the resulted responses in the time domain are then evaluated using ISO-2631 criteria to assess the passenger comfortability.Â Â Â